Pemberian Probiotik Pada Pengolahan Limbah Udang Yang Dimasak dengan Tekanan Tinggi Terhadap Kandungan Protein Kasar dan serat Kasar [Giving Probiotic At Prawn Waste Processing With High Pressure Cooked for Crude Protein and Crude Fibre Content] - Agustono Agustono; Ika Agustin Handyani; Mirni Lamid (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
Abstract Feed is one of the factors determines the success of a fish farm. Feed-quality feed stuffs that require high quality also, which still rely on imports, especially fish meal and soybean oilcake. Effort to reduce dependence on import of feed stuff is searching for alternative feed stuffs that the quality is quite good, cheap, easily obtained and can reduce cost of production. One of the feed stuff as an alternative source of animal protein feed that need to be examined is the prawn waste. Prawn waste meal enough potential to be used as fish feed with a crude protein content 45.29% and 17.59% crude fiber was alternative feed stuff for fish meal. The usage of prawn waste as a feed stuff should be through the handling and processing to further improve the nutrient value of waste. Prawn waste processing in this research consists of two ways, that is waste cooking prawn on the high pressure (100 kpa), and conducted fermentation by using probiotic. The existence of microorganisms activity during the fermentation process will cause changes of feed stuffs either through physically and chemicals. Probiotic is a microbe colony that is rich in celulolytic, lignolytic and proteolytic bacteria. The aim of this research is to know the influence probiotic on the prawn waste cooked with high pressure to increase the protein content and to decrease the crude fiber content. Method as used in the research is experimental method. Experiment design that used at research is Completely Randomized Design with 4 treatments and replicates 5 times. To get the data is conducted procsimat analysis on the crude protein content and crude fibers from each experimental unit. That result data analyzed with the Analysis of Varian continued with Duncan's Multiple Range Test. The results of research is known that dosaged probiotic at process of prawn waste cooked fermentation not different to crude protein contents of the waste cook fermented prawn. Crude fiber content of the waste cook fermented prawn using probiotik (P1, P2, P3) has decreased if compared with waste cooking fermented prawn without using probiotic (P0)